Agenesis of Dorsal Pancreas Associated with Periampullary Pancreaticobiliary Type Adenocarcinoma - Sannappa, Raghu M; Buragohain, Jadunath; Sarma, Dipti; Saikia, Uma Kaimal; Choudhury, Bipul Kumar (JOP. Journal of the Pancreas, 2014)
Context Agenesis of the dorsal pancreas is one of the rare congenital malformations of pancreas. The association of agenesis of the dorsal pancreas with pancreatic tumors is extremely rare and only around 9 cases being reported till date. Case report We report a case of a fifty one year old woman with an agenesis of the dorsal pancreas with periampullary pancreaticobiliary adenocarcinoma. She presented with features of obstructive jaundice without pain abdomen or fever. Laboratory data showed conjugated hyperbilirubinemia, raised alkaline phosphatase and impaired glucose tolerance. Ultrasound abdomen showed periampullary mass. MRI abdomen and MRCP demonstrated dorsal agenesis of the pancreas, dilated intra and extra hepatic bile ducts with narrowing of distal CBD with periampullary mass. Pancreatic tumor was considered as preoperative diagnosis, and pancreaticoduodenectomy was performed. Histopathology confirmed pancreaticobiliary type of adenocarcinoma. Conclusion A rare case of dorsal agenesis of the pancreas with periampullary pancreaticobiliary type of adenocarcinoma was presented. Therefore this case therefore merits reference as a rare clinical presentation. Image: Immunohistochemical staining of poorly differentiated tumor showing positivity for proliferative marker Ki-67.